P136 Association between histological indices and ulcerative colitis activity measures among patients in the HICKORY (etrolizumab) open-label induction cohort. (25th January 2019) - Peyrin-Biroulet, L; Feagan, B; Pai, R K; Arulmani, U; Boruvka, A; Oh, Y S; Scherl, A; Scalori, A; Arrisi, P; Tole, S; Rubin, D T
Abstract: Background: Cross-sectional studies in UC have shown an association between histological and clinical measures of disease activity, but few longitudinal studies have evaluated this relationship. 1, 2 Using data from the open-label induction (OLI) cohort of HICKORY, 3 we evaluated the correlation between histological changes and established disease activity measures at end of induction (Week 14). Methods: Baseline and Week 14 biopsies were scored by 4 central readers using the Robarts histopathology index (RHI) and the Nancy histological index (NHI) in patients who had active baseline histology (NHI > 1 and RHI > 3) and complete scoring at Week 14 ( n = 97). Binary Week 14 histological outcomes were characterised by presence or absence of neutrophils (NHI ≤ 1 or RHI ≤ 3 and Geboes subgrades 2B.0/3.0). Pairwise associations were quantified by Spearman correlation (ρ; for correlation between change from baseline scores) and Cohen's kappa coefficients (κ; for agreement among Week 14 outcomes). ΔRHI and ΔNHI were compared with determine the presence of a minimal clinically important difference (MCID) in Mayo Clinic score (MCS; ∆MCS ≥ 3). MCS endoscopic subscore (ES) was used to assess endoscopy. Results: At Week 14, 22% (21/97), 23% (22/97) and 8% (8/97) of patients achieved resolution of neutrophilic inflammation, endoscopic improvement (ES ≤ 1) and endoscopic remission (ES=0), respectively; NHI ≤ 1 was achieved in 55% (12/22) of patients with ES ≤ 1 and 75% (6/8) of patients with ES = 0. ΔNHI and ΔRHI were highly correlated (ρ = 0.91). There was little to no association between laboratory results and ΔNHI/ΔRHI/ΔES (Figure 1A). A weak correlation was seen between ΔNHI/ΔRHI and ΔES (ρ = 0.26–0.27) and between ΔNHI/ΔRHI and change in rectal bleeding and stool frequency. NHI, RHI and ES agreement with symptomatic outcomes were weak to moderate (κ = 0.28–0.45; Figure 1B). Difference in the mean grouped by achievement of ΔMCS ≥3 suggests MCIDs in ΔNHI and ΔRHI of 1 and 9, respectively (Table 1). Figure 1. (A) Pairwise Spearman correlation coefficients between change from baseline scores at Week 14 and disease activity measures and (B) Pairwise Cohen's kappa coefficients among Week 14 outcomes. Abstract PO136 – Table 1. Baseline and Change from Baseline in NHI and RHI by Achievement of MCID in MCS (∆MCS≥3) in NHI- and RHI-evaluable Patients Conclusions: The analysis showed no associations between changes in histological scores and changes in laboratory results, a weak correlation between changes in histological and endoscopic scores, and a weak to modest correlation between histological scores and symptoms at the end of induction. References 1. Bessissow T, Lemmens B, Ferrante M, et al. Prognostic value of serologic and histologic markers on clinical relapse in ulcerative colitis patients with mucosal healing, Am J Gastroenterol, 2012;107:1684-92. 2. Christensen B, Hanauer SB, Erlich J, et al . Histologic normalization occurs in ulcerative colitis and is associated with improved clinical outcomes. Clin Gastroenterol Hepatol 2017;15:1557–64. 3 Rubin DT, Feagan BG, Peyrin-Biroulet L, et al . Tu2006—etrolizumab induction therapy improves histologic outcomes in anti-TNF-failed patients with ulcerative colitis: results from the Hickory Open-Label Induction cohort. Gastroenterology . 2018;S-1366